Design movement in Tagore's Santiniketan : alpana - an experiment in aestheticism - Ghosh, Swati (New Delhi, India : Niyogi Books, 2019)
On Alpana, decorative art of floor and wall paintings, with reference to Santiniketan, India.
Includes bibliographical references and index.
Keywords: Alpana (Art) -- India -- Santiniketan; Alpana (Art) -- Themes, motives; Alpana (Art) -- India -- Santiniketan; Alpana (Art) -- Themes, motives; Alpana (Art)